Paleolithic Diet, Abdominal Adiposity, and Systemic Low-grade Chronic Inflammation. Associations in Observational Studies and a Randomized Controlled Trial - Carrera Bastos, Pedro (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
Background: Systemic low-grade chronic inflammation (SLGCI), commonly assessed by biomarkers such as total leukocyte count, neutrophil-to-lymphocyte ratio (NLR), and C-reactive protein (CRP), is associated with cardiometabolic disease, and both are associated with diet and abdominal adiposity. The Paleolithic diet may reduce SLGCI by reducing abdominal adiposity and through direct effects on the immune system. Aims: This thesis explores the relationship between SLGCI, abdominal adiposity, and the Paleolithic diet using both observational and interventional designs. Methods: Papers I and II compared CRP and total adiponectin (an adipokine often inversely associated with SLGCI, abdominal adiposity, and cardiometabolic disease) between Kitavans, a lean Melanesian population with a Paleolithic-type diet and an apparent absence of cardiometabolic disease, and Swedish controls. Paper III was a 2-year RCT comparing a healthy diet without cereal grains, a main characteristic of the Paleolithic diet, versus one emphasizing whole grains, each with and without long-term exercise, on waist circumference, a proxy for abdominal adiposity. Paper IV analyzed associations between the Paleolithic Diet Fraction (PDF), a dietary pattern measure defined as the proportion of food intake consistent with a Paleolithic diet, and inflammatory biomarkers (total leukocyte count, NLR, and CRP) in 23,250 participants from the Malmö Diet and Cancer Study. Results: In Papers I and II, Kitavans had lower CRP and lower total adiponectin than Swedish controls. In Paper III, the no-grain group without exercise showed the largest, albeit non-significant, reduction in waist circumference. In Paper IV, PDF was inversely associated with all inflammatory biomarkers, independent of adiposity and lifestyle factors. Conclusion: A relatively higher intake of Paleolithic foods is associated with lower levels of SLGCI, potentially through both reduced abdominal adiposity and direct effects on the immune system. The low adiponectin levels among Kitavans raise questions about its presumed inverse association with SLGCI, abdominal adiposity, and cardiometabolic disease.
Keywords: Systemic Low-grade Chronic Inflammation; Paleolithic Diet; C-Reactive Protein; Adiponectin; Waist Circumference